SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane and application thereof

By using dichlorodimethylsilane and dichlorodiocene in SiC ceramics to form polyzirconium carbonsilane and reacting with trimethylaminoborane monomer to form SiC/ZrC/ZrB2 complex-phase ceramic pioneer, SiC is solved The problem of uneven ablation and doping of ceramics under high temperature environments has achieved the preparation of ceramics with high zirconium content and low oxygen content, which has the advantages of low cost.

CN119161584APending Publication Date: 2024-12-20NINGBO ZHONGXING NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311704436.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing SiC ceramics are severely ablated in high temperature environments, resulting in loss of working capacity, and traditional doping methods are difficult to achieve uniform doping and high oxygen content.

Method used

Dichlorodimethylsilane and dichlorodiocene are used to form polyzirconium carbosilane by sodium dechlorination in an organic solvent, and then solvothermal reaction with trimethylaminoborane monomer under an inert atmosphere to form SiC/ZrC /ZrB2 complex-phase ceramic pioneer polyboron zirconium carbosilane achieves uniform doping of boron and zirconium elements.

Benefits of technology

The preparation of SiC/ZrC/ZrB2 composite ceramic pioneer with high zirconium content is achieved, which reduces the oxygen content, solves the problem of uneven doping, and has a lower preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161584A_ABST
    Figure CN119161584A_ABST
Patent Text Reader

Abstract

The invention relates to SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane and application thereof, and a preparation method of the SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane comprises the following steps: preparing polyzirconium carbosilane from dichlorodimethylsilane and zirconocene dichloride; the preparation method comprises the following steps: preparing a trimethylamine borane monomer from methylamine and BCl3; and carrying out solvothermal reaction on the polyzirconium carbosilane and a trimethylamino borane monomer to prepare the polyboron zirconium carbosilane. The invention also comprises an application of the SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane. According to the invention, the contents of boron and zirconium elements are adjustable, so that the boron and zirconium elements are effectively doped in the polymer, and the product can have high zirconium content; the raw materials used in the method do not contain oxygen, so that the oxygen content of the product can be reduced, and low-oxygen and oxygen-free products are expected to be obtained; the method has the advantages of simple reaction conditions and low preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite ceramic precursor and application thereof, in particular to a SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane and application thereof. Background Art

[0002] Silicon carbide (SiC) ceramics and their composite materials have excellent properties such as low density, high temperature resistance, oxidation resistance, corrosion resistance, and creep resistance. They are widely used in high-tech fields such as aviation, aerospace, national defense, and nuclear industry. However, SiC is severely ablated in a specific high-temperature environment and will eventually lose its ability to work. At present, researchers mainly introduce zirconium, hafnium, titanium, boron, aluminum and other elements into SiC ceramics to improve the heat resistance of the material under high temperature conditions and enhance its oxidation resistance.

[0003] There are two main ways to introduce heterogeneous elements into SiC ceramics, one is physical doping, and the other is to introduce heterogeneous elements into the molecular structure of the precursor. Compared with the former, the latter method can achieve uniform doping of heterogeneous elements at the atomic scale while maintaining excellent machinability, making the corresponding ceramic performance more uniform and consistent. At present, the most commonly used precursor for the preparation of SiC ceramics (especially SiC fibers) is polycarbosilane. In order to improve the performance of SiC ceramics, researchers have conducted a lot of modification and doping studies on polycarbosilane precursors. For example, Cao Shuwei et al. used liquid polysilicon carbosilane to react with zirconium acetylacetonate at 360°C to obtain zirconium-containing polycarbosilane. The zirconium content in the zirconium-containing precursor synthesized by this method is generally below 2wt%, and the raw material acetylacetone contains a high oxygen content, which makes the synthesized zirconium-containing polycarbosilane have a high oxygen content. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a SiC / ZrC / ZrB2 composite ceramic precursor polyboronitrile carbosilane with a high zirconium content and its application.

[0005] The technical solution adopted by the present invention to solve the technical problem is as follows: a SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane, the preparation method of which comprises the following steps:

[0006] (1) Dichlorodimethylsilane and dichlorozirconocene are reacted in an organic solvent under the dechlorination of sodium to generate polyzirconium carbosilane (PZCS) through catalytic rearrangement polymerization; methylamine and BCl3 are reacted in an organic solvent under an inert atmosphere to generate trimethylamine borane monomer (B(NHCH3)3);

[0007] (2) PZCS, B(NHCH3)3 and an organic solvent are added into a high-pressure reactor and subjected to a solvent thermal reaction under an inert atmosphere to obtain polyborazolium carbosilane (PBZCS).

[0008] The reaction between methylamine and BCl3 is the dehydrogenation reaction of the B-Cl bond and the NH bond. Step (1) realizes the effective doping of boron and zirconium elements in the polymer respectively; step (2) obtains a ceramic precursor containing both boron and zirconium through a solvent thermal reaction.

[0009] Preferably, in step (1) or step (2), the organic solvent is toluene and / or xylene.

[0010] By adopting the above technical solution, the reaction can proceed smoothly.

[0011] Preferably, in step (2), the mass ratio of PZCS to B(NHCH3)3 is 1:0.1 to 1:10.

[0012] By adopting the above technical solution, PBZCS can be obtained; the ratio of boron to zirconium can be adjusted within a large range.

[0013] More preferably, in step (2), the mass ratio of PZCS to B(NHCH3)3 is 1:0.5 to 1:5.

[0014] By adopting the above technical solution, PBZCS can be obtained; the ratio of boron to zirconium can be adjusted within a large range.

[0015] Preferably, in step (2), the total mass of PZCS and B(NHCH3)3 is 30 to 80% of the mass of the organic solvent.

[0016] By adopting the above technical solution, the reaction can proceed smoothly.

[0017] More preferably, in step (2), the total mass of PZCS and B(NHCH3)3 is 50 to 70% of the mass of the organic solvent.

[0018] By adopting the above technical solution, the reaction can proceed smoothly.

[0019] Preferably, in step (2), the temperature of the solvent thermal reaction is controlled by heating to 150-250°C at a heating rate of 1-20°C / min and keeping warm for 5-15h, then heating to 350-430°C at a heating rate of 1-20°C / min and reacting for 5-20h, and then cooling naturally.

[0020] By adopting the above technical solution, the reaction can proceed smoothly.

[0021] More preferably, in step (2), the temperature of the solvent thermal reaction is controlled by heating to 160-220°C at a heating rate of 3-15°C / min and keeping the temperature for 5-10h, then heating to 350-400°C at a heating rate of 3-15°C / min and reacting for 8-18h, and then cooling naturally.

[0022] By adopting the above technical solution, the reaction can proceed smoothly.

[0023] Preferably, the preparation method of PZCS is: adding sodium to an organic solvent, heating, stirring, condensing and refluxing, adding dichlorozirconocene after the sodium forms sodium sand, and then dropping dichlorodimethylsilane, and obtaining a dark brown solid product PZCS after the reaction is completed.

[0024] By adopting the above technical solution, the reaction can proceed smoothly.

[0025] More preferably, in the preparation method of PZCS, the mass ratio of sodium to organic solvent is 1:5 to 1:20.

[0026] By adopting the above technical solution, the reaction can proceed smoothly.

[0027] Further preferably, in the preparation method of PZCS, the mass ratio of sodium to organic solvent is 1:8 to 1:15.

[0028] By adopting the above technical solution, the reaction can proceed smoothly.

[0029] More preferably, in the method for preparing PZCS, the heating temperature is 90-110°C.

[0030] By adopting the above technical solution, the reaction can proceed smoothly.

[0031] More preferably, in the method for preparing PZCS, the heating temperature is 100-110°C.

[0032] By adopting the above technical solution, the reaction can proceed smoothly.

[0033] More preferably, in the preparation method of PZCS, the mass ratio of zirconocene dichloride to sodium is 1:1.5 to 1:8.

[0034] By adopting the above technical solution, the reaction can proceed smoothly.

[0035] Further preferably, in the preparation method of PZCS, the mass ratio of zirconocene dichloride to sodium is 1:1.5 to 1:5.

[0036] By adopting the above technical solution, the reaction can proceed smoothly.

[0037] More preferably, in the preparation method of PZCS, the mass ratio of dichlorozirconocene to dichlorodimethylsilane is 1:3 to 1:15.

[0038] By adopting the above technical solution, the reaction can be smoothly carried out, and the content of zirconium in the obtained PZCS can be adjusted by adjusting the ratio.

[0039] Further preferably, in the preparation method of PZCS, the mass ratio of dichlorozirconocene to dichlorodimethylsilane is 1:5 to 1:10.

[0040] By adopting the above technical solution, the reaction can be smoothly carried out, and the content of zirconium in the obtained PZCS can be adjusted by adjusting the ratio.

[0041] More preferably, in the method for preparing PZCS, the dropping speed is 0.1 to 10 kg / h.

[0042] By adopting the above technical solution, the reaction can proceed smoothly.

[0043] More preferably, in the method for preparing PZCS, the dropping speed is 0.5 to 5 kg / h.

[0044] By adopting the above technical solution, the reaction can proceed smoothly.

[0045] More preferably, in the preparation method of PZCS, after all the dichlorodimethylsilane is added dropwise, the reaction is carried out for 10 to 80 hours.

[0046] By adopting the above technical solution, the reaction can proceed smoothly.

[0047] Further preferably, in the preparation method of PZCS, after all the dichlorodimethylsilane is added dropwise, the reaction is carried out for 15 to 50 hours.

[0048] By adopting the above technical solution, the reaction can proceed smoothly.

[0049] Preferably, the preparation method of B(NHCH3)3 is: passing boron trichloride into an organic solvent, stirring, condensing and reflux, and then passing methylamine to react, and B(NHCH3)3 is obtained after the reaction is completed.

[0050] By adopting the above technical solution, the reaction can proceed smoothly.

[0051] More preferably, in the method for preparing B(NHCH3)3, the mass ratio of the boron trichloride to the organic solvent is 1:5 to 1:20.

[0052] By adopting the above technical solution, the reaction can proceed smoothly, and the content of boron in the obtained B(NHCH3)3 can be adjusted by adjusting the ratio.

[0053] Further preferably, in the method for preparing B(NHCH3)3, the mass ratio of the boron trichloride to the organic solvent is 1:5 to 1:15.

[0054] By adopting the above technical solution, the reaction can proceed smoothly, and the content of boron in the obtained B(NHCH3)3 can be adjusted by adjusting the ratio.

[0055] More preferably, in the method for preparing B(NHCH3)3, the introduction rate of boron trichloride is 0.5 to 5 kg / h.

[0056] By adopting the above technical solution, the reaction can proceed smoothly.

[0057] Further preferably, in the method for preparing B(NHCH3)3, the introduction rate of boron trichloride is 1 to 5 kg / h.

[0058] By adopting the above technical solution, the reaction can proceed smoothly.

[0059] More preferably, in the method for preparing B(NHCH3)3, the mass ratio of the boron trichloride to the methylamine is 1:0.5 to 1:5.

[0060] By adopting the above technical solution, the reaction can proceed smoothly.

[0061] Further preferably, in the method for preparing B(NHCH3)3, the mass ratio of the boron trichloride to the methylamine is 1:0.5 to 1:4.

[0062] By adopting the above technical solution, the reaction can proceed smoothly.

[0063] More preferably, in the method for preparing B(NHCH3)3, the methylamine introduction rate is 0.1 to 5 kg / h.

[0064] By adopting the above technical solution, the reaction can proceed smoothly.

[0065] Further preferably, in the method for preparing B(NHCH3)3, the methylamine introduction rate is 0.5 to 5 kg / h.

[0066] By adopting the above technical solution, the reaction can proceed smoothly.

[0067] More preferably, in the preparation method of B(NHCH3)3, after all the methylamine is introduced, the reaction is carried out for 1 to 40 hours.

[0068] By adopting the above technical solution, the reaction can proceed smoothly.

[0069] Further preferably, in the preparation method of B(NHCH3)3, after all the methylamine is introduced, the reaction is carried out for 15 to 50 hours.

[0070] By adopting the above technical solution, the reaction can proceed smoothly.

[0071] The SiC / ZrC / ZrB2 composite ceramic precursor PBZCS of the present invention is used to sinter the PBZCS in an inert atmosphere to obtain SiC / ZrC / ZrB2 composite ceramics.

[0072] By adopting the above technical solution, SiC / ZrC / ZrB2 composite ceramics can be produced.

[0073] Preferably, the sintering temperature is 1100-1800°C.

[0074] By adopting the above technical solution, the reaction can proceed smoothly.

[0075] More preferably, the sintering temperature is 1400-1700°C.

[0076] By adopting the above technical solution, the reaction can proceed smoothly.

[0077] Preferably, the sintering holding time is 0.5 to 5 hours.

[0078] By adopting the above technical solution, the reaction can proceed smoothly.

[0079] More preferably, the sintering holding time is 1 to 3 hours.

[0080] By adopting the above technical solution, the reaction can proceed smoothly.

[0081] Preferably, the heating rate of sintering is 5-50° C. / min.

[0082] By adopting the above technical solution, the reaction can proceed smoothly.

[0083] More preferably, the heating rate of sintering is 5 to 20° C. / min.

[0084] By adopting the above technical solution, the reaction can proceed smoothly.

[0085] The application of the SiC / ZrC / ZrB2 composite ceramic precursor PBZCS of the present invention is to dissolve the PBZCS in an organic solvent, remove the precipitate in the solution, and remove the solvent to obtain a PBZCS concentrate; the PBZCS concentrate is subjected to melt spinning, electron beam irradiation infusibility treatment, and sintering in an inert atmosphere to obtain a SiC / ZrC / ZrB2 composite ceramic fiber.

[0086] By adopting the above technical solution, SiC / ZrC / ZrB2 composite ceramic fibers can be produced.

[0087] Preferably, the melt spinning temperature is 200-350°C.

[0088] By adopting the above technical solution, melt spinning can be carried out smoothly.

[0089] More preferably, the melt spinning temperature is 250-350°C.

[0090] By adopting the above technical solution, melt spinning can be carried out smoothly.

[0091] Preferably, the heat preservation treatment is performed for 1 to 10 hours before melt spinning.

[0092] By adopting the above technical solution, melt spinning can be carried out smoothly.

[0093] More preferably, the heat preservation treatment is performed for 3 to 7 hours before melt spinning.

[0094] By adopting the above technical solution, melt spinning can be carried out smoothly.

[0095] Preferably, the irradiation dose of the electron beam irradiation is 10 to 50 mGy.

[0096] By adopting the above technical solution, a better processing effect is achieved.

[0097] More preferably, the irradiation dose of electron beam irradiation is 10 to 25 mGy.

[0098] By adopting the above technical solution, a better processing effect is achieved.

[0099] Preferably, the sintering temperature is 1300-1800°C.

[0100] By adopting the above technical solution, the reaction can proceed smoothly.

[0101] More preferably, the sintering temperature is 1400-1600°C.

[0102] By adopting the above technical solution, the reaction can proceed smoothly.

[0103] Preferably, the sintering holding time is 0.5 to 5 hours.

[0104] By adopting the above technical solution, the reaction can proceed smoothly.

[0105] More preferably, the sintering holding time is 1 to 3 hours.

[0106] By adopting the above technical solution, the reaction can proceed smoothly.

[0107] Preferably, the heating rate of sintering is 0.1-50° C. / min.

[0108] By adopting the above technical solution, the reaction can proceed smoothly.

[0109] More preferably, the heating rate of sintering is 1-20°C / min.

[0110] By adopting the above technical solution, the reaction can proceed smoothly.

[0111] The present invention uses dichlorodimethylsilane, dichlorozirconocene and metallic sodium as raw materials, and while sodium is condensed and dechlorinated, Zr is introduced into the molecular structure of polycarbosilane through a catalytic rearrangement reaction, thereby synthesizing polyzirconosilane in one step; and B is introduced into the molecular structure through a demethylamine reaction of trimethylaminoborane and polyzirconosilane, thereby synthesizing polyboron zirconosilane, a precursor of SiC / ZrC / ZrB2 composite ceramic fibers. Effective doping of boron and zirconium elements in polymers is achieved, and the content of boron and zirconium elements is adjustable.

[0112] The beneficial effects of the present invention are:

[0113] (1) The present invention provides a SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane, in which the content of boron and zirconium elements is adjustable, thereby achieving effective doping of boron and zirconium elements in the polymer, and better solving the problem of uneven doping in the traditional powder doping process, and the product can have a high zirconium content;

[0114] (2) The raw materials used in the present invention do not contain oxygen, which can reduce the oxygen content of the product and is expected to further obtain low-oxygen and oxygen-free ceramic products;

[0115] (3) It has the advantages of simple reaction conditions and low preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0116] Figure 1 This is an optical photograph of the PBZCS of Example 1 of the present invention.

[0117] Figure 2 This is a result diagram of infrared spectrum analysis of PBZCS of Example 1 of the present invention using KBr pellet method.

[0118] Figure 3 This is a result diagram of infrared spectrum analysis of PBZCS of Example 2 of the present invention using KBr pellet method.

[0119] Figure 4 This is an optical photograph of the SiC / ZrC / ZrB2 composite ceramic fiber prepared in Example 2 of the present invention.

[0120] Figure 5 This is the XRD spectrum of the SiC / ZrC / ZrB2 ceramics prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0121] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0122] The raw materials used in the examples of the present invention are all obtained through conventional commercial channels.

[0123] Example 1

[0124] The preparation method of the SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane in this embodiment includes the following steps:

[0125] (1) Preparation of PZCS and B(NHCH3)3:

[0126] Preparation of PZCS: Under nitrogen protection, 490g of metallic sodium and 5000g of anhydrous xylene were added to a double-layer glass kettle with a condensation reflux device, and then the system was quickly heated to 100°C. After stirring to form sodium sand, 150g of dichlorodimonocene zirconium was directly added to the system, and then 1000g of dichlorodimethylsilane was dripped into the reaction system at a dripping speed of 2kg / h. After the dripping was completed, the reaction was carried out for 25h, and then naturally cooled to room temperature. After conventional filtration and solvent removal, PZCS was obtained;

[0127] Preparation of B(NHCH3)3: Under nitrogen protection, 5000g of anhydrous xylene is put into a double-layer glass kettle with a condensation reflux device, and then 458g of boron trichloride is introduced at a rate of 3kg / h and stirred continuously. After the introduction of boron trichloride, 649g of methylamine gas is directly introduced into the system at a rate of 2kg / h. After all the methylamine is introduced, the reaction is carried out for 20h, and then naturally cooled to room temperature; the system solution is finally filtered and the solvent is removed by conventional means to obtain trimethylamine borane monomer;

[0128] (2) 203 g PZCS, 98 g B(NHCH3)3, and 600 g xylene were placed in a 2 L autoclave, the air in the autoclave was replaced with high-purity nitrogen, the autoclave was sealed, the temperature was increased to 180°C at a heating rate of 5°C / min, the temperature was kept at that temperature for 5 h, and then the temperature was increased to 400°C at a heating rate of 5°C / min and the temperature was kept at that temperature for 10 h, and then the temperature was naturally cooled to room temperature; the xylene in the autoclave reaction system was removed under the protection of high-purity N2 to obtain PBZCS.

[0129] The appearance of the PBZCS in this embodiment is as follows Figure 1 As shown, the softening point is 124°C and the ceramic yield is 51%.

[0130] The infrared spectrum analysis of PBZCS in this example was performed using the KBr tablet method. The results are as follows: Figure 2 As shown. The wave number is 1254cm -1 The absorption peak corresponding to the Si-CH3 bond, wave number 3425cm -1 The absorption peak corresponding to the NH bond, wave number 1420cm -1 Corresponding to the absorption peak of BN bond (very weak). Wave number 2100cm -1 The absorption peak corresponding to the Si-H bond. The Si-H content of the product PBZCS is 0.36, and the Si-H content of the raw material PZCS is 0.7. The above analysis shows that the trimethylamino borane monomer reacts with polyzirconium carbosilane to generate polyboron zirconium carbosilane.

[0131] Example 2

[0132] The preparation method of the SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane in this embodiment includes the following steps:

[0133] (1) Preparation of PZCS and B(NHCH3)3: The same process as in Example 1 was used;

[0134] (2) 198 g PZCS, 147 g B(NHCH3)3, and 600 g xylene were placed in a 2 L autoclave, the air in the autoclave was replaced with high-purity nitrogen, the autoclave was sealed, the temperature was increased to 180°C at a heating rate of 5°C / min, the temperature was kept at that temperature for 5 h, and then the temperature was increased to 400°C at a heating rate of 5°C / min and the temperature was kept at that temperature for 10 h, and then the reaction mixture was naturally cooled to room temperature; the xylene in the autoclave reaction system was removed under the protection of high-purity N2 to obtain PBZCS.

[0135] The softening point of the obtained PBZCS is 139 °C, and the ceramic yield is 63%.

[0136] The infrared spectrum analysis of PBZCS in this example was performed using the KBr tablet method. The results are as follows: Figure 3As shown. The wave number is 1254cm -1 The absorption peak corresponding to the Si-CH3 bond, wave number 3425cm -1 The absorption peak corresponding to the NH bond, wave number 1420cm -1 Corresponding to the absorption peak of BN bond (very weak). Wave number 2100cm -1 The absorption peak corresponding to the Si-H bond. The Si-H content of the product PBZCS is 0.31, and the Si-H content of the raw material PZCS is 0.7.

[0137] The application of polyboron zirconium carbosilane, a precursor of SiC / ZrC / ZrB2 composite ceramics in this embodiment, is used to prepare SiC / ZrC / ZrB2 composite ceramic fibers. The specific process is as follows:

[0138] (s1) dissolving PBZCS in xylene, removing precipitates from the solution by conventional filtration, and removing the solvent by reduced pressure distillation to obtain 100 g of PBZCS spinning material with a softening point of 162° C.;

[0139] (s2) adding the PBZCS spinning material obtained in (s1) into a melt spinning tank, heating to 350° C. and keeping the temperature constant for 1 h under the protection of high-purity nitrogen, performing a degassing treatment and then melt spinning to obtain PBZCS raw fibers;

[0140] (s3) subjecting the PBZCS fibrils to electron beam non-melting cross-linking under the protection of high-purity nitrogen, with an irradiation dose of 20 mGy, to obtain PBZCS cross-linked fibers;

[0141] (s4) The PBZCS cross-linked fiber is placed in a high-temperature pyrolysis furnace, and after vacuum replacement three times, the temperature is raised to 1400°C at a heating rate of 1°C / min and kept at this temperature for 1 h. After the pyrolysis furnace is naturally cooled to room temperature, SiC / ZrC / ZrB2 composite ceramic fibers can be obtained. Figure 4 shown.

[0142] The obtained SiC / ZrC / ZrB2 composite ceramic fiber has a diameter of 11.5 μm and a density of 2.12 g / cm 3 The average tensile strength of the fiber is 2.6 GPa, and the modulus is 285 GPa. The mass content of B element in the fiber is 2.63% and the mass content of Zr element is 4.58% by inductively coupled plasma emission spectroscopy (ICP).

[0143] Example 3

[0144] The preparation method of the SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane in this embodiment includes the following steps:

[0145] (1) Preparation of PZCS and B(NHCH3)3: The same process as in Example 1 was used;

[0146] (2) 205 g PZCS, 207 g B(NHCH3)3, and 600 g xylene were placed in a 2 L autoclave, the air in the autoclave was replaced with high-purity nitrogen, the autoclave was sealed, the temperature was increased to 180°C at a heating rate of 5°C / min, the temperature was kept at that temperature for 5 h, and then the temperature was increased to 400°C at a heating rate of 5°C / min and the temperature was kept at that temperature for 10 h, and then the reaction mixture was naturally cooled to room temperature; the xylene in the autoclave reaction system was removed under the protection of high-purity N2 to obtain PBZCS.

[0147] The softening point of the obtained PBZCS is 132 °C, and the ceramic yield is 61%.

[0148] The application of polyboron zirconium carbosilane, a precursor of SiC / ZrC / ZrB2 composite ceramics in this embodiment - is used to prepare SiC / ZrC / ZrB2 composite ceramics. The specific process is as follows:

[0149] 2 g of PBZCS was placed in a crucible and placed in a sintering furnace. Under Ar protection, the furnace temperature was raised to 1600°C at a heating rate of 10°C / min and kept at this temperature for 1 hour to obtain SiC ceramics containing B and Zr elements.

[0150] The boron content of the obtained ceramic is 3.45% by mass, and the zirconium content is 5.73% by mass. The XRD test results of the obtained ceramic are shown in Figure 5 The test results show that diffraction peaks appear at 2θ angles of 35.6°, 59.9°, and 71.8°, which are consistent with the characteristic peaks of SiC; diffraction peaks appear at 33.5°, 38.7°, and 72.3°, which are consistent with the characteristic peaks of ZrC; diffraction peaks appear at 38.7°, 55.95°, and 66.7°, which are consistent with the characteristic peaks of ZrB2, proving that the obtained solid is a SiC / ZrC / ZrB2 ceramic product.

Claims

1. A SiC / ZrC / ZrB2 composite ceramic precursor polyboron zirconium carbosilane, characterized in that: The preparation method comprises the following steps: (1) Dichlorodimethylsilane and dichlorozirconocene are reacted in an organic solvent under the dechlorination of sodium to generate polyzirconium carbosilane through catalytic rearrangement polymerization; methylamine and BCl3 are used as raw materials to react in an organic solvent under an inert atmosphere to generate trimethylamine borane monomer; (2) Adding polyzirconium carbosilane, trimethylamino borane monomer and organic solvent into a high-pressure reactor, and carrying out a solvent thermal reaction under an inert atmosphere to obtain polyzirconium borocarbosilane.

2. The SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to claim 1, characterized in that: In step (1) or step (2), the organic solvent is toluene and / or xylene; in step (2), the mass ratio of the polyzirconium carbosilane to the trimethylamine borane monomer is 1:0.1-1:10; in step (2), the total mass of the polyzirconium carbosilane and the trimethylamine borane monomer is 30-80% of the mass of the organic solvent; in step (2), the temperature of the solvent thermal reaction is controlled by heating to 150-250°C at a heating rate of 1-20°C / min and keeping the temperature for 5-15h, then heating to 350-430°C at a heating rate of 1-20°C / min and reacting for 5-20h, and then cooling naturally.

3. The SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to claim 1 or 2, characterized in that: The preparation method of the polyzirconium carbosilane is as follows: sodium is added into an organic solvent, heated and stirred to condense and reflux, and after the sodium forms sodium sand, dichlorodimonocene zirconium is added, and then dichlorodimethylsilane is added dropwise, and after the reaction is completed, a dark brown solid product polyzirconium carbosilane is obtained.

4. The SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to claim 3, characterized in that: In the preparation method of polyzirconium carbosilane: the mass ratio of sodium to organic solvent is 1:5~1:20; the heating temperature is 90~110°C; the mass ratio of dichlorozirconocene to sodium is 1:1.5~1:8; the mass ratio of dichlorozirconocene to dichlorodimethylsilane is 1:3~1:15; the dropping speed is 0.1~10kg / h; after all the dichlorodimethylsilane is dropped, the reaction is carried out for 10~80h.

5. The SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to claim 1 or 2, characterized in that: The preparation method of the trimethylamine borane monomer is as follows: boron trichloride is introduced into an organic solvent, stirred, condensed and refluxed, and then methylamine is introduced to react, and the trimethylamine borane monomer is obtained after the reaction is completed.

6. The SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to claim 5, characterized in that: In the preparation method of the trimethylamino borane monomer, the mass ratio of the boron trichloride to the organic solvent is 1:5-1:20; the introduction rate of the boron trichloride is 0.5-5 kg / h; the mass ratio of the boron trichloride to the methylamine is 1:0.5-1:5; the introduction rate of the methylamine is 0.1-5 kg / h; after all the methylamine is introduced, the reaction is carried out for 1-40 hours.

7. The use of SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to any one of claims 1 to 6, characterized in that: The polyborazuric carbosilane is sintered in an inert atmosphere to obtain SiC / ZrC / ZrB2 composite ceramics.

8. The use of the SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to claim 7, characterized in that: The sintering temperature is 1100-1800° C.; the sintering heat preservation time is 0.5-5 hours; and the sintering heating rate is 5-50° C. / min.

9. The use of SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to any one of claims 1 to 6, characterized in that: The polyborane zirconium carbon silane is dissolved in an organic solvent, the precipitate in the solution is removed, and the solvent is removed to obtain a polyborane zirconium carbon silane concentrate; the polyborane zirconium carbon silane concentrate is melt-spun, subjected to electron beam irradiation infusibility treatment, and sintered in an inert atmosphere to obtain a SiC / ZrC / ZrB2 composite ceramic fiber.

10. The use of the SiC / ZrC / ZrB2 composite ceramic precursor polyzirconium borocarbosilane according to claim 9, characterized in that: The melt spinning temperature is 200-350°C; the heat preservation treatment before melt spinning is 1-10 hours; the irradiation dose of electron beam irradiation is 10-50 mGy; the sintering temperature is 1300-1800°C; the heat preservation time of sintering is 0.5-5 hours; and the heating rate of sintering is 0.1-50°C / min.

Citation Information

Cited By

  • Preparation method and application of ZrB2 / ZrC / SiC complex-phase precursor material with high ceramic yield

    CN120059242A

  • Preparation method and application of low-cost polyzirconium carbosilane precursor

    CN123003886A